2015
DOI: 10.1016/j.mib.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in (p)ppGpp metabolism and effectors

Abstract: Bacteria produce guanosine tetraphosphate and pentaphosphate, collectively named (p)ppGpp, in response to a variety of environmental stimuli. These two remarkable molecules regulate many cellular processes, including the central dogma processes and metabolism, to ensure survival and adaptation. Work in Escherichia coli laid the foundation for understanding the molecular details of (p)ppGpp and its cellular functions. As recent studies expand to other species, it is apparent that there exists considerable varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
168
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 74 publications
1
168
0
8
Order By: Relevance
“…The stringent response is a highly conserved mechanism that enables bacteria (1)(2)(3) and plant chloroplasts (4)(5)(6) to respond to nutrient (i.e., amino acid) limitations. However, recent work has indicated that guanosine tetraphosphate (ppGpp) and guanosine pentaphosphate (pppGpp) [collectively named "(p)ppGpp"] also impact other, nonstringent response processes such as virulence (7)(8)(9) as well as persister (10,11) and biofilm formation (12).…”
mentioning
confidence: 99%
“…The stringent response is a highly conserved mechanism that enables bacteria (1)(2)(3) and plant chloroplasts (4)(5)(6) to respond to nutrient (i.e., amino acid) limitations. However, recent work has indicated that guanosine tetraphosphate (ppGpp) and guanosine pentaphosphate (pppGpp) [collectively named "(p)ppGpp"] also impact other, nonstringent response processes such as virulence (7)(8)(9) as well as persister (10,11) and biofilm formation (12).…”
mentioning
confidence: 99%
“…Accumulation of (p)ppGpp induces a wide range of physiological alterations that affect many important cellular processes such as DNA replication, transcription, translation, and metabolism (27). In E. coli, (p)ppGpp and a coregulator, DksA, bind directly to RNA polymerase to inhibit or activate transcription (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…(p)ppGpp has also been shown be important for the association of alternative sigma factors with the RNA polymerase core (30). In the Gram-positive bacterium B. subtilis, (p)ppGpp's effects on transcriptional regulation occur primarily through modulation of GTP levels (27). GTP is one of the substrates for (p)ppGpp syn- thesis, so as (p)ppGpp levels rise, GTP becomes depleted.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNAP dissociation can allow alternative sigma factors to bind RNAP, leading to the regulation of distinct promoter sets important for adjustment to new environmental conditions (3, 6). In some bacteria, ppGpp executes the stringent response in a different way, not involving RNAP binding (7,8).The overall processes of the stringent response are similar in a wide variety of bacteria, but structural and functional variations occur. Some bacterial genomes carry a single spoT/relA gene that encodes a bifunctional protein comprising a ppGpp synthetase and a hydrolase domain (9-11).…”
mentioning
confidence: 99%
“…In addition, RNAP dissociation can allow alternative sigma factors to bind RNAP, leading to the regulation of distinct promoter sets important for adjustment to new environmental conditions (3, 6). In some bacteria, ppGpp executes the stringent response in a different way, not involving RNAP binding (7,8).…”
mentioning
confidence: 99%